1996
DOI: 10.1007/bf00119733
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of different chemical methods for cros-linking collagen gel, films and sponges

Abstract: Collagen-based films and sponges are widely used as biomaterials. The rate of their biodegradation can be reduced by treating them with different cross-linking agents. The efficiency of different reticulation procedures on thermal stability (measured by differential scanning calorimetry) and susceptibility to bacterial collagenase digestion of the final material (films or sponges) is compared. The chemical agents used on collagen gels or directly on collagen sponges and films were glutaraldehyde (GTA), hexamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
145
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(150 citation statements)
references
References 21 publications
5
145
0
Order By: Relevance
“…Over the years, a number of cross-linking approaches (chemical, physical and biological) have been investigated (30); however, at present, there is not a commonly accepted ideal cross-linking treatment for collagen-derived bio-prosthesis. It has been recently reported that chemical stabilization through bifunctional agents (as epoxy compounds) leads to scaffolds that are characterized by thermal, structural, physical, and mechanical properties similar to those of native tissues (31).…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, a number of cross-linking approaches (chemical, physical and biological) have been investigated (30); however, at present, there is not a commonly accepted ideal cross-linking treatment for collagen-derived bio-prosthesis. It has been recently reported that chemical stabilization through bifunctional agents (as epoxy compounds) leads to scaffolds that are characterized by thermal, structural, physical, and mechanical properties similar to those of native tissues (31).…”
Section: Discussionmentioning
confidence: 99%
“…The greater amount of glutamic acid and aspartic acid in BF collagen could explain the different physical-chemical properties of the HACSMs composed of higher BF collagen ratios, for example reduction in pore size and swelling ratio, enhancement in tensile strength, resistance to collagenase, and thermal stability. The EDC cross-linking system is frequently used in the porous collagen materials [5,9,11,14,15], which has shown better biocompatibility than glutaraldehyde (GA) [9]. In principle, the EDC cross-linking takes place by the reaction between carboxyl groups of glutamic acid and aspartic acid and generated stable amide bonds [9,11,[13][14][15]24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The TNP-Gly to be modified, on the other hand, carried amino groups. Therefore, EDC/NHS was chosen to serve as the activator for the coupling reaction [30][31][32][33]. As shown in Figure 4, consulting the test results of different EDC/NHS ratios, the ratio of EDC: NHS = 4:1 was chosen for further experiments.…”
Section: Chosen Of Chip Activatormentioning
confidence: 99%